2020
DOI: 10.1016/j.chest.2019.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Disease Severity and Quality of Life in Patients With Idiopathic Pulmonary Fibrosis

Abstract: BACKGROUND: Limited data are available on the association between clinically measured disease severity markers and quality of life (QOL) in idiopathic pulmonary fibrosis (IPF). The study examined the associations between objective disease severity metrics and QOL in a contemporary IPF population. METHODS: This study evaluated baseline data from patients enrolled in the multicenter, USbased Idiopathic Pulmonary Fibrosis Prospective Outcomes Registry between June 2014 and July 2018. Disease severity metrics incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Overall, our study population has better HRQL scores than existing local or overseas cohorts ( 14 , 24 ). The most likely explanation is the milder disease severity in our patient population, as evidenced by the higher FVC and DLCO %pred values compared with other studies, with almost two-thirds of our patients being GAP Stage I ( 25 ). Consistent with other studies, IPF patients have the poorest HRQL scores in terms of EQ5D-3L utility value, K-BILD total, ‘psychological’, ‘breathlessness and activities domain’ compared to CTD-ILD and other ILD patients ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Overall, our study population has better HRQL scores than existing local or overseas cohorts ( 14 , 24 ). The most likely explanation is the milder disease severity in our patient population, as evidenced by the higher FVC and DLCO %pred values compared with other studies, with almost two-thirds of our patients being GAP Stage I ( 25 ). Consistent with other studies, IPF patients have the poorest HRQL scores in terms of EQ5D-3L utility value, K-BILD total, ‘psychological’, ‘breathlessness and activities domain’ compared to CTD-ILD and other ILD patients ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 42%
“…Our study showed that the DLCO %pred, but not FVC %pred, is a significant predictor of poor K-BILD total, ‘psychological’ and ‘breathlessness and activities’ domains in ILD patients. Indeed, a lower baseline DLCO %pred is associated not only with poorer HRQL ( 25 , 34 ) but also with future HRQL deterioration ( 16 , 41 ). Even though the degree of reduction in DLCO usually mirrors the corresponding drop in FVC, a severe reduction in DLCO may represent the presence of pulmonary hypertension on top of lung parenchymal destruction from ILD, and pulmonary hypertension has been shown to decrease the quality of life in IPF patients ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that measuring frailty might give insight into the physical constitution of patients suffering from lung diseases (40). We chose supplemental oxygen use at rest since this is a parameter that most patients are well aware of and it is one objective marker for disease severity used also in other studies (41,42). Additionally, patients included in this study were recruited during psychosocial evaluation before listing for transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The MCID on the SGRQ was defined as a mean four-point change in total score, as proposed by Jones PW et al [ 16 ] The SGRQ has been validated and commonly used in patients with IPF. [ 17 ]…”
Section: Methodsmentioning
confidence: 99%